An Autopsy Case of Pancreatic Cystadenocarcinoma - SASAKI, Yoshihiro; UMEMURA, Yoshifumi; FUKUHARA, Yasuki; TSUCHIDA, Hiroshi; MATSUMOTO, Kazuhito; ITO, Fumiya; KUDO, Masaru; KAWAHARA, Reiko (Japanese Journal of National Medical Services, 1989)
The patient was a 84-year-old man with chief complaint of abdominal distention and anorexia. On laboratory data, various kind of tumor makers were makedly increased, especially CA19-9, NCC-ST-439 and SLX, CEA, CA125 and Du-Pan-2 were also slightly to moderately elevated. Abdominal CT study revealed a mass lesion with irregular surface and multiple cysts in pancreatic body. Aspirated ascites contained adenocarcinoma cells. By these findings, pancreatic cystadenocarcinoma was highly suspected. He died 2 weeks after admission and autopsy was performed. The pancreas was from its body to tail, occupied by the huge tumor which had multiple cysts and nodular lesions. Metastasis was found in liver, lungs, peritoneum and numerous lymphnodes. Histologically, the cyst were lined by atypical cuboid or columnar foamy epithelial cells, some of which grew in a papillary fashion into the lumen. The tumor cells also infiltrated into adjacent interstitial tissue associated with fibrosis. The neoplastic cells contained mucus in its cytoplasm and the diagnosis of pancreatic mucinous cystadenocarcinoma was made.